Business networks, entrepreneurial branding and innovation : strategies for promoting start-up success in Botswana and South Africa - Bornman, Dawie Alwyn Jacobus (University of Pretoria, 2025)
Thesis (PhD (Entrepreneurship))--University of Pretoria, 2024.